A Bibliometric Analysis of Management Bioenergy Research Using Vosviewer Application - Herman Soegoto; Eddy Soeryanto Soegoto; Senny Luckyardi; Agis Abdi Rafdhi (Universitas Pendidikan Indonesia, 2022)
This study aims at analyzing and demonstrating bibliometric data analysis step by step using VOSViewer systematically. Step-by-step analysis was provided to make first-time users access and utilize VOSViewers more easily. This study provides data analysis regarding management bioenergy and its development throughout five years (2017–2021) by utilizing mapping tools in the VOSViewer. The method used was qualitative descriptive to describe the bibliometric analysis performance by producing network visualization of the chosen topic. From the search results, 1000 relevant published journals were found, ranging from 2017–2021, which were then grouped into five categories according to their published year. After grouping the journal data, we discovered that the total number of articles published on the topic of bioenergy management from 2017 to 2021 was 180. As a result, it conclude that management bioenergy is a field that can be combined with another field to be studied. This way, there is a lot of opportunities to find novelties in this topic. Furthermore, this study is expected to serve as a resource for researchers conducting research and determining the research theme.